Near-infrared light-responsive hybrid hydrogels for the synergistic chemo-photothermal therapy of oral cancer. Issue 40 (12th October 2021) - Wu, Yongzhi; Chen, Fangman; Huang, Nengwen; Li, Jinjin; Wu, Chenzhou; Tan, Bowen; Liu, Yunkun; Li, Longjiang; Yang, Chao; Shao, Dan; Liao, Jinfeng
Abstract : A near-infrared light-responsive hybrid hydrogel was injected in the tumor site. IR820 could not only produce local heat for photothermal therapy, but also generate singlet oxygen to induce the degradation of MSNs for controllable drug release. Abstract : Light-stimulus-responsive therapies have been recognized as a promising strategy for the efficient and safe treatment of oral squamous cell carcinoma (OSCC). Hydrogels have emerged as a promising multifunctional platform combining localized drug delivery and sustained drug release with multimodal properties for combined OSCC therapy. However, inaccurate drug release and limited light-absorption efficiency have hindered their on-demand chemo-photothermal applications. To tackle these problems, an injectable and near-infrared (NIR) light-responsive hybrid system was developed by incorporating light-responsive mesoporous silica nanoparticles (MSNs) as doxorubicin (DOX) carriers into the IR820/methylcellulose hydrogel networks for chemophotothermal therapy. Under NIR radiation, the incorporated IR820, a new green cyanine dye, was excited to induce photothermal effects against tumor cells. Meanwhile, MSNs achieved self-degradation-controlled DOX release via the cleavage of diselenide bonds induced by reactive oxygen species. Through the combination of chemotherapy and phototherapy, a long-lasting synergistic anti-tumor effect was achieved in vitro and in vivo with less toxicity. These findings demonstrate the potential of light-responsive hydrogels as a multifunctional platform for accurate synergistic chemophotothermal treatment of OSCC.